Interlaboratory Comparison of Forming Limit Curves for Hot Stamping of High Strength Steels - Pellegrini, D.; Lechler, Jürgen; Ghiotti, Andrea; Bruschi, S.; Merklein, Marion (SheMet'09, Proceedings of the 13th International Conference on Sheet Metal, 2009)
The paper presents the approaches followed by two labs - LFT at the University of Erlangen-Nuremberg (Germany) and DIMEG at University of Padua (Italy) - in evaluating formability limits of 22MnB5 sheets when processed under hot stamping conditions. Details about the two testing apparatuses and the testing procedures are outlined, and the results in terms of Forming Limit Curves FLC compared and critically commented. © (2009) Trans Tech Publications, Switzerland.
LFT Import::2019-08-05 (1565)
Keywords: Forming limit curve; High strength steel; Hot stamping